Coupled kinetic-like opinion dynamics models - Oestereich, André Luis (2020)
In this work we will present a series of coupled opinion dynamics models. We will study the interplay between the community structure and the opinion dynamics. This interplay will be studied by means of two distinct models. Both these models were solved by means of an approximation in the network structure. We will also see a model with unchanging individual preferences in complex networks. Hysteresis and disorder-induced order have emerged in this model. Finally, we will see an epidemic model in which the opinions dictate the vaccination probability. This model presents a double-edge effect where an increment in the pro-vaccine fraction of the population can decrease the long-term vaccine coverage.